Flammes trompeuses : interprétation de quelques photos d’archives de scènes iconoclastes - Julien Volper (OpenEdition, 2019)
Regarding Central Africa, photographic archives are not readily illustrating the particular subject of the destruction of ritual objects, as operated by Catholics and Protestants missionaries. This paper focuses on three cases of stakes supposed to have been used for burning “pagan” objects. These specific case studies helps to analyze the difference between historical reality and interpretative mistake or smokescreen.